Must do better to halt malnutrition - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
The 2004 edition of the United Nations Food and Agriculture Organization s State of Food Insecurity in the World sets out to monitor progress towards the goal laid down by the 1996 World Food Summit that of halving the number of hungry people on the